The Effect of Various Kinds of Mulch on the Growth and Production of Chili Plants - Fitri Yetty Zairani; Burlian Hasani; Laili Nisfuriah; Dali Dali; Rastuti Kalasari; Gamal Abd. Nasser (Universitas Muhammadiyah Palembang, 2023)
This study aims to determine the effect of mulching on the growth and production of chili plants. This study used a randomized block design, with 6 treatments and 4 replications. One treatment 4 sample plants. The treatments used are as follows: M0: Without using mulch; M1= Using reed mulch; M2 = Using rice straw mulch; M3 = Use silver black plastic mulch; M4 = Using clear plastic mulch; M5 = Use clear mulch covered with newspaper. The variables observed were plant height, number of secondary branches, fruit weight per plant, dry plant weight and production per hectare. Based on the results of the research that has been carried out, it was concluded that: black silver plastic mulch treatment gave the best effect on the growth and production of chili plants, such as plant height, number of secondary branches, fruit weight of each plant, dry weight of plant trunks, and production per hectare. Meanwhile, the production of red chilies per hectare produced by silver black plastic mulch has a higher capacity of 8.02 tons/ha and the lowest yield is 3.01 tons/ha of clear plastic mulch.